Effect of MgO addition on the physical properties and reactivity of the spray-dried oxygen carriers prepared with a high content of NiO and Al2O3. (15th March 2015) - Baek, Jeom-In; Yang, Seug-Ran; Eom, Tae Hyoung; Lee, Joong Beom; Ryu, Chong Kul
Graphical abstract: Highlights: Mg-added spray-dried oxygen carriers with high NiO content were characterized. γ-Al2 O3 -based oxygen carrier had superior performances to α-Al2 O3 -based ones. Excess MgO addition led significant grain growth and bigger grain formation. MgO addition inhibited NiAl2 O4 formation resulting in higher reactivity. Oxygen carrier derived from γ-Al2 O3 mixed with MgO showed best performances. Abstract: The performance of an oxygen carrier (OC) in chemical looping combustion (CLC) is largely influenced by the support used. In this study, the effect of MgO addition on the physical properties and oxygen transfer reactivity of spray-dried NiO OCs was investigated to suggest support composition for performance improvement. Various OCs were prepared using 70 wt% NiO and 0, 4.2, and 8.4 wt% MgO balanced with α-Al2 O3 or γ-Al2 O3 . MgO addition hindered NiAl2 O4 formation and left more amount of NiO, resulting in enhanced reactivity. OCs derived from γ-Al2 O3 in combination with MgO showed superior performances. The strong NiO–support interaction of the OC derived from γ-Al2 O3 in combination with MgO, even at a lower calcination temperature, led less grain growth and higher reactivity. Although the OC added with 8.4 wt% MgO had higher mechanical strength, it showed much slower oxygen transfer rate due to very low porosity and the formation of much bigger grains by sintering. Agglomeration between particles was more significant in the OCs with lower porosity and bigger grains regardless of MgO addition. The OC derived from γ-Al2 O3 mixed with 4.2 wt% MgO showed the best performance: spherical shape, high mechanical strength, high oxygen transfer reactivity, complete regeneration, and no agglomeration. Its oxygen transfer capacity, 12.2 wt%, is far superior to the ones in literature for Mg-added spray-dried NiO OCs. Carbon deposition was largely affected by the CH4 concentration and the amount of remained oxygen rather than reduction rate or the amount of Mg. Carbon deposition could be suppressed at a high H2 O concentration. Unless excess MgO is added, this work suggests that γ-Al2 O3 mixed with MgO could be a suitable support material to obtain a Mg-added spray-dried NiO OC with high attrition resistance, higher reactivity, and no agglomeration.